Usages et impacts des espèces arborescentes dans les exploitations cacaoyères de l’Indénié-Djuablin, Côte d’Ivoire - Ménéké Distel Kougbo; François Malan Djah; Amadou Lamine Diop; Sylvie Konan Amenan; Mathieu Dogba (VertigO)
Tree species have always played an important role in tropical cocoa farms. However, their survival is threatened by changes in farming practices. This study aims to understand the interactions between farmers in Indénié-Djuablin and the tree species that they save or introduce in their cocoa farms. To do this, an inventory of these species was carried out in 54 cocoa farms selected on the basis of the area and density of tree species. An individual semi-structured survey was then conducted with the cocoa farm owners to find out how they perceive and use the tree species found on their farms. In these cocoa farms, 63 tree species were inventoried that were used in four categories of use : food, timber, medicinal and fuelwood. Furthermore, 64.06% of these wood species are perceived as having positive or negative impacts on the development of cocoa trees. The timber like Tiama (Entandrophragma angolense), Bété (Mansonia altissima) and Iroko (Milicia excelsa) is valued for the excellent shade that is beneficial to young cocoa trees and the improvement of soil fertility while medicinal plants like Emien (Alstonia boonei), Ilomba (Pycnanthus angolensis) and Akpi (Ricinodendron heudelotii) are perceived as creating excessive shade and as potential hosts of crop pests. Some woody plants that are detrimental to the development of cocoa trees are therefore maintained in cocoa farms for specific uses. Taking this aspect into account in any agroforestry project would make it possible to sustainably reconcile agricultural production, conservation of plant diversity and resource development.